Expression of c-kit in human osteosarcoma and its relevance as a prognostic marker. Issue 7 (3rd October 2006) - Sulzbacher, Irene; Birner, Peter; Toma, Cyril; Wick, Nikolaus; Mazal, Peter R
Abstract : Aims: To examine the prognostic relevance of c-kit expression in human osteosarcomas and to evaluate the mutation status in exon 9 and exon 11 of the c-kit gene. Methods: c-kit expression was examined in 100 human osteosarcomas by immunohistochemistry using paraffin embedded tumour tissues, and capillary sequencing of genomic DNA was performed to search for mutations in exons 9 and 11 of the c-kit gene. Results: 20 osteosarcomas showed c-kit expression ranging from 5% to 90% (mean 5.9%; SD 16.74%). Furthermore, DNA sequences of exon 9 and exon 11 of the c-kit gene were not altered in these tumours. Overall and disease free survival analysis did not reveal any differences between patients with osteosarcoma with c-kit expression and those with c-kit negative tumours. Conclusions: C-kit expression is not a prognostic marker in patients with osteosarcoma. The protein expression is not linked to mutations in exon 9 or exon 11 of the c-kit gene. Therefore, these exons may not function as targets for treatment modalities based on the suppression of c-kit tyrosine kinase activity.